Local foods can meet micronutrient needs for women in urban Burkina Faso, but only if rarely consumed micronutrient-dense foods are included in daily diets: A linear programming exercise - Arimond, Mary; Vitta, Bineti S.; Martin-Prével, Yves; Moursi, Mourad; Dewey, Kathryn G. (Wiley, 2018)
Women of reproductive age are at nutritional risk due to their need for nutrient‐dense diets. Risk is further elevated in resource‐poor environments. In one such environment, we evaluated feasibility of meeting micronutrient needs of women of reproductive age using local foods alone or using local foods and supplements, while minimizing cost. Based on dietary recall data from Ouagadougou, we used linear programming to identify the lowest cost options for meeting 10 micronutrient intake recommendations, while also meeting energy needs and following an acceptable macronutrient intake pattern. We modeled scenarios with maximum intake per food item constrained at the 75th percentile of reported intake and also with more liberal maxima based on recommended portions per day, with and without the addition of supplements. Some scenarios allowed only commonly consumed foods (reported on at least 10% of recall days). We modeled separately for pregnant, lactating, and nonpregnant, nonlactating women. With maxima constrained to the 75th percentile, all micronutrient needs could be met with local foods but only when several nutrient‐dense but rarely consumed items were included in daily diets. When only commonly consumed foods were allowed, micronutrient needs could not be met without supplements. When larger amounts of common animal‐source foods were allowed, all needs could be met for nonpregnant, nonlactating women but not for pregnant or lactating women, without supplements. We conclude that locally available foods could meet micronutrient needs but that to achieve this, strategies would be needed to increase consistent availability in markets, consistent economic access, and demand.